Disturbed sleep and fatigue in occupational burnout - Ekstedt, Mirjam; Söderström, Marie; Åkerstedt, Torbjörn; Nilsson, Jens; Søndergaard, Hans-Peter; Aleksander, Perski (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'The purpose of this study was to investigate sleep with polysomnography and self-ratings and the diurnal pattern of sleepiness and fatigue in a group suffering from severe occupational burnout. ' ' METHOD ': 'Twelve white-collar workers on long-term sick leave (>3 months) and 12 healthy controls with high and low scores on the Shirom Melamed Burnout Questionnaire (SMBQ) were included. A 1-night polysomnographic recording (after habituation) was carried out at home, and sleepiness and mental fatigue were rated at different times of the day for weekdays and the weekend. Precipitating factors at the time of the illness at work and real life were considered, and different dimensions of occupational fatigue were described. A repeated-measures analysis of variance using two or three within group factors was used to analyze the data. ' ' RESULTS ': 'The main polysomnographic findings were more arousals and sleep fragmentation, more wake time and stage-1 sleep, lower sleep efficiency, less slow wave sleep and rapid eye movement sleep, and a lower delta power density in nonrapid eye movement sleep in the burnout group. The burnout patients showed pronounced sleepiness and mental fatigue at most times of the day for weekdays without reduction during weekends. The precipitating factor was occupational stress (psychiatric interview), and work stress indicators were increased. ' ' CONCLUSIONS ': 'Occupational burnout is characterized by impaired sleep. It is suggested that impaired sleep may play a role in the development of fatigue or exhaustion in burnout.
Keywords: arousal; burnout; disturbed sleep; fatigue; mental fatigue; occupational burnout; polysomnography; sleep; sleepiness